Work Environment and Work Ability as Predictors of Employee Performance and Job Satisfaction: Evidence from a Public Health Center in Indonesia - Laili, Noor; Geraldina, Ira; Gunarto, Muji (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study investigates the influence of the work environment and work ability on employee performance and examines the mediating role of job satisfaction in this relationship, with empirical evidence drawn from the UPTD Muara Komam Health Center in Indonesia. The research was motivated by the need to enhance healthcare service quality through improved human resource performance, amid concerns over suboptimal working conditions and employee competencies. Using a quantitative approach, data were collected from 63 randomly selected employees via validated and reliable questionnaires. The Structural Equation Modeling (SEM) method was employed using SmartPLS software for data analysis. Results demonstrate that both the work environment and work ability significantly influence employee performance. Furthermore, job satisfaction serves as a critical mediator, reinforcing the positive impact of these two factors on performance outcomes. The findings suggest that a supportive work environment and a competent workforce not only directly enhance performance but also do so indirectly through increased job satisfaction. The study offers valuable managerial implications, recommending that health sector administrators improve workplace facilities, foster collegial work relationships, and invest in continuous training to optimize employee performance and satisfaction.